Specifically Regulated Pesticides in Florida: Bromacil - Frederick M. Fishel (EDIS)
Bromacil is a general use pesticide that is marketed in Florida under many names and is used on sites such as citrus, pineapple, and industrial areas. This 2-page document discusses the characteristics and use of bromacil. Written by Frederick M. Fishel and published by the UF/IFAS Agronomy Department, May 2018. https://edis.ifas.ufl.edu/pi112